PENGENALAN CLOUD COMPUTING SEBAGAI PENUNJANG PEMBELAJARAN PADA PESANTREN NAFIDATUNNAJAH - Chandra Alim; Ahmad Fauzi; Herwis Gultom (Universitas Pamulang, 2025)
The need for affordable, flexible, and efficient information technology is increasingly pressing in this rapidly evolving digital era. Cloud computing is one innovation that addresses this challenge. With this technology, users can use the internet to manage, store, and access data and applications without the need for local hardware. The activity, themed